Three dimensional response of RC bridges under spatially varying seismic excitation - methodology - Peña Ramos, Carlos Enrique; Haldar, Achintya (Journal of Structural Engineering, 2024)
A novel approach to study realistic nonlinear seismic response behavior of three-dimensional (3-D) long - and/or multi-span reinforced concrete bridges is presented in this paper with the help of six steps. It incorporates up- to-date requirements suggested in international seismic design guidelines. The ground supports are excited by point specific and correlated three-component acceleration time histories of a design earthquake. The algorithm rigorously considers spatial variability in the ground excitation caused by wave passage, wave incoherence and local soil conditions. Bridges are represented by 3-D finite element models. Also presented are analytical models for bidirectional plastic hinges at piers, soil-foundation interface elements that account for soil dynamic stiffness at each ground support, and the effects of far-field and near-field location of the epicenter. The relevant response parameter is considered to be the rotational ductility demand in piers. To study the differences in ductility demand of the piers under spatially varying and uniform seismic excitations, a new parameter , ductility index, is introduced. The numerical procedures are clarified and important observations are made with the help of numerous examples in the companion paper.